Long‐term Geophysical Monitoring of Simulated Clandestine Graves using Electrical and Ground Penetrating Radar Methods: 4–6 Years After Burial1. Issue 2 (4th January 2016) - Pringle, Jamie K.; Jervis, John R.; Roberts, Daniel; Dick, Henry C.; Wisniewski, Kristopher D.; Cassidy, Nigel J.; Cassella, John P.
Abstract: This ongoing monitoring study provides forensic search teams with systematic geophysical data over simulated clandestine graves for comparison to active cases. Simulated "wrapped, " "naked, " and "control" burials were created. Multiple geophysical surveys were collected over 6 years, here showing data from 4 to 6 years after burial. Electrical resistivity (twin electrode and ERI), multifrequency GPR, grave and background soil water were collected. Resistivity surveys revealed that the naked burial had low‐resistivity anomalies up to year four but then difficult to image, whereas the wrapped burial had consistent large high‐resistivity anomalies. GPR 110‐ to 900‐MHz frequency surveys showed that the wrapped burial could be detected throughout, but the naked burial was either not detectable or poorly resolved. 225‐MHz frequency GPR data were optimal. Soil water analyses showed decreasing (years 4 to 5) to background (year 6) conductivity values. Results suggest both resistivity and GPR surveying if burial style unknown, with winter to spring surveys optimal and increasingly important as time increases.